Inland fisheries conservation pathways in Hill streams - Singh, Atul K (Journal of the Inland Fisheries Society of India, 2025)
Fisheries resources in the Himalayan and high-altitude regions-including Jammu & Kashmir, Himachal Pradesh, Uttarakhand, Sikkim, Arunachal Pradesh, Nagaland, and Meghalaya-are primarily distributed in upland rivers, streams, lakes, and reservoirs characterized by cold waters (5-20 °C) with high dissolved oxygen. Native fish species inhabiting these hill streams deliver critical ecosystem services: provisioning (food and livelihood security), cultural and spiritual values, and supporting and regulatory functions within the Indian Himalayan biodiversity hotspot.